2021
DOI: 10.3961/jpmph.21.120
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Physical Factors of Parents and Children on Stunting at Birth Among Newborns in Indonesia

Abstract: Objectives: This study examined stunting at birth and its associations with physical factors of parents and children in Indonesia.Methods: This study analyzed secondary data from the national cross-sectional Indonesian Basic Health Survey 2018, conducted across 34 provinces and 514 districts/cities. Birth length data were available for 756 newborns. Univariable, bivariable, and multivariable logistic regression analyses were performed to determine associations between the physical factors of parents and childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
15

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 20 publications
3
32
1
15
Order By: Relevance
“…Children whose parents are both < 20 years old are twice as likely to be stunted at birth. Women who gave birth for the first time at the age of less than 27 years had lower levels of maturity (Finlay, Özaltin, & Canning, 2011) Mothers whose first pregnancy was in the 27-29 year age range were more likely to live in better sanitary conditions, have higher levels of education, have higher socioeconomic status, have a partner, and live in urban areas (Sari & Sartika, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Children whose parents are both < 20 years old are twice as likely to be stunted at birth. Women who gave birth for the first time at the age of less than 27 years had lower levels of maturity (Finlay, Özaltin, & Canning, 2011) Mothers whose first pregnancy was in the 27-29 year age range were more likely to live in better sanitary conditions, have higher levels of education, have higher socioeconomic status, have a partner, and live in urban areas (Sari & Sartika, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A study suggested that the father's height can affect a newborn's likelihood of inheriting a gene that affects bone growth throughout pregnancy, while the mother's height can affect a newborn's likelihood of inheriting a gene that affects bone growth at a later period during pregnancy [9]. Mother's height genetically affects child growth [6].…”
Section: Relationship Between Mother's Height With Stunting Incidentmentioning
confidence: 99%
“…Risiko kehamilan akan terjadi pada ibu yang melahirkan dengan usia kurang dari 20 tahun dan lebih dari 35 tahun erat kaitannya dengan terjadinya preeclampsia, pertumbuhan janin yang buruk. Ini menunjukkan bahwa usia ibu pada kehamilan dapat mengakibatkan hasil kelahiran yang buruk yang menghambat pertumbuhan potensial anak (Sari and Sartika, 2021).…”
Section: Pembahasanunclassified
“…Studi terhadap 55 negara menunjukkan bahwa meningkatkan usia pada kehamilan pertama menjadi 27-29 dapat menurunkan angka kematian bayi dan hasil kesehatan anak yang merugikan (Stunting, kurus, anemia, diare). Ibu yang kehamilan pertamanya berada dalam kisaran usia 27-29 (kelahiran pertama tertunda) lebih cenderung hidup dalam kondisi sanitasi yang lebih baik, memiliki tingkat pendidikan tinggi, memiliki status sosial ekonomi yang lebih tinggi, memiliki pasangan, dan tinggal di daerah perkotaan (Sari and Sartika, 2021).…”
Section: Pembahasanunclassified